Outcome After Modified Grice-Green Procedure (SAMBB) for Arthritic Acquired Adult Flatfoot. (November 2020) - Mosca, Massimiliano; Caravelli, Silvio; Vocale, Emanuele; Massimi, Simone; Fuiano, Mario; Grassi, Alberto; Ceccarelli, Francesco; Zaffagnini, Stefano
Background: Adult acquired flatfoot deformity is a well-known and recognized cause of pain and disability. The purpose of this retrospective study was to describe radiographic and clinical outcomes of the modified mini bone block distraction subtalar arthrodesis (SAMBB) in adult patients affected by adult flatfoot with subtalar joint osteoarthritis at a midterm mean follow-up. Methods: A retrospective review of our database identified patients. Radiological imaging was used to evaluate angular corrections (Meary's angle [MA], talar coverage angle [TC], and calcaneal pitch angle [CP]) to assess the rate of union and highlight the possible progression of arthritis in nearby joints. Clinical evaluation was performed at the time of surgery and at the final follow-up using the American Orthopaedic Foot & Ankle Society (AOFAS) ankle-hindfoot score. Sixty-two feet were evaluated at a mean follow-up of 6.2 ± 4.2 years. Results: The AOFAS score improved from a mean value of 48.1 ± 6.1 to a postoperative average score of 87.7 ± 5. CP, TC, and MA showed a postoperative improvement to 17.7 ± 2.1, 2.9 ± 0.7, and 0.6 ± 0.6 degrees, respectively, at the final follow-up, and all deformities were corrected. Five complications (8%) were reported: 1 major and 4 minor. No graft reabsorption, sural nerve neuralgia, or donor site morbidity was recorded. Conclusion: To our knowledge, this study is the first report of a modified Grice-Green technique (SAMBB) that is a safe and effective treatment of flatfoot in the adult with subtalar arthritis. Level of evidence: Level IV, retrospective case series.